COMORBIDITY ATTENTION DEFICIT AND HYPERACTIVITY DISORDER WITH GAME ADDICTION - Ria Adriani (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2020)
Child and adolescents with Attention Deficit Hyperactivity Disorder (ADHD) who experience game addiction are 3 times higher risk compared with other populations. Parents often report their inability to limit, regulate and supervise the use of games. The relationship between intentions in ADHD children with game addiction is reciprocal reaction. Wherein the symptoms of inattention trigger the emergence of game addiction and game addiction causes disruption of existing attentions to last longer. individuals with ADHD also have a high impulsivity and inability to think about the impact on something done. Impulsivity which is owned can cause difficulties in controlling excessive game which produces negative consequences. Impulsivity is the endophenotype underlying the relationship between ADHD and addiction. As such, effective interventions for impulsivity should be given immediately to adolescents with ADHD to reduce the risk of comorbid addiction games. Adolescents with ADHD have a higher hostility as well as those who experience game addiction so that the higher the hostility of adolescents with ADHD the more vulnerable. Hostility and impulsivity are important factors that clarify the comorbidities of ADHD and addiction. Pharmacotherapy treatment in ADHD and game addiction based on the underlying psychopathology is impulsivity, compulsivity as in the obsessive compulsive spectrum and based on high comorbidity in this disorder. Non-pharmacotherapy modalities in the form of CBT psychotherapy, METCBT, motivational interviews. Combination therapy becomes the basic modality for adequate management.Keywords:.ADHD, game addiction, impulsive.